PERKEMBANGAN PENERIMAAN PAJAK DI INDONESIA - WILIYAN PRADANA, IPUT Wiliyan (Jurnal Akuntansi AKUNESA, 2013)
The Purpose of this study is to know the Indonesia’s tax income grow. This study usedcomparative methods, that compare the same variable but more than two sample, orcompared in the different time. This study is use a secunder data. The result for this study isshow that Indonesia’s tax income growth is good enough. It can be seen from the Indonesia’stax income always increase every year. It caused that the tax reform give a big effect to theIndonesia’s tax income growth.Keywords : Tax Income Growth, Tax Reform, comparative methods